Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/1596-3519.122687
|View full text |Cite
|
Sign up to set email alerts
|

Breaking bad news in clinical setting - health professionals′ experience and perceived competence in southwestern Nigeria: A cross sectional study

Abstract: It appears that the large proportion of the respondents in this study were unconsciously incompetent in BBN in view of the low level of training and little or no knowledge of well known protocols for BBN even though self-rated competence is high. Continuous medical education in communication skills among health personnel in Nigeria is advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 23 publications
8
25
0
1
Order By: Relevance
“…BBN is described in the clinical setting as the delivery of any news that drastically and negatively alters the patient's view of his or her life (Adebayo et al, 2013). In the event of an OHCA, the individuals concerned are the family on scene that are being informed of their relative's likely or confirmed death.…”
Section: What Is Bbn?mentioning
confidence: 99%
See 1 more Smart Citation
“…BBN is described in the clinical setting as the delivery of any news that drastically and negatively alters the patient's view of his or her life (Adebayo et al, 2013). In the event of an OHCA, the individuals concerned are the family on scene that are being informed of their relative's likely or confirmed death.…”
Section: What Is Bbn?mentioning
confidence: 99%
“…Evidence suggests a widespread unconscious incompetence among health professionals when BBN and this is believed to be a result of poor or non-existent training (Adebayo et al, 2013). Studies have found training courses to be useful in improving clinician competence and confidence in BBN (Eid et al, 2009;Wuensch et al, 2013;Pang et al, 2015;Reed et al, 2015).…”
Section: Training In Bbnmentioning
confidence: 99%
“…In Botswana from 2011 to 2013 on the pediatric ward at Princess Marina Hospital (PMH), the mortality rate in the neonatal unit was high at 20% (259/1275) and in the pediatric medical ward, the mortality rate was 6% (250/2183) (Patlakwe, 2013), yet medical staff and students at the University of Botswana have not received formal training in communicating bad news and there is only one adult-focused palliative care-trained physician for the entire hospital. A study in Nigeria showed that doctors were unconsciously incompetent in breaking bad news because of a low level of training and little to no knowledge of recommended communication strategies (Adebayo et al, 2013). There is an urgent unmet need for medical students, especially in LMIC, to learn how to deliver bad news and communicate effectively with patients and families.…”
Section: Introductionmentioning
confidence: 99%
“…Poor communication skills of an inexperienced clinician can ruin the goal of providing support to the patient and eliciting patient's collaboration for future treatment. Studies have demonstrated that many doctors lack competence as well as confidence in their ability to divulge bad news and there is necessity to provide didactic training [35]. Several protocols have been devised to guide the doctors for imparting this skill [36][37][38].…”
Section: Breaking Bad Newsmentioning
confidence: 99%